2022
DOI: 10.1007/s12540-021-01138-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of a Laser Cladded Coating and Surface Texture on Tribological Performance Under Dry Sliding and Starved Lubrication

Abstract: Fe-based alloy coating was laser cladded on gray cast iron using Ni-Cu alloy as an intermediate layer. The cross section of the laser cladded coating was characterized by optical microscopy (OM), scanning electron microscopy (SEM) equipped with energy dispersive spectrometry (EDS), X-ray diffraction (XRD), and a Vickers hardness tester. A microdimple texture was created by reciprocating an electrolyte jet with prefabricated mask (REJP) machining on an Fe-based alloy coating. The tribological performances of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nowadays, Laser Surface Texturing (LST), has become a well-known surface to improve the tribological characteristics of contact interface. Researchers have carried out a great deal of research on the tribological behaviour related to LST [13][14][15][16][17][18]. However, these studies are all carried out in the case of no current input, and the research related to LST under current-carrying condition is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Laser Surface Texturing (LST), has become a well-known surface to improve the tribological characteristics of contact interface. Researchers have carried out a great deal of research on the tribological behaviour related to LST [13][14][15][16][17][18]. However, these studies are all carried out in the case of no current input, and the research related to LST under current-carrying condition is rarely reported.…”
Section: Introductionmentioning
confidence: 99%